Copy Number Variation of Human Satellite III (1q12) With Aging - Ershova, Elizaveta S.; Malinovskaya, Elena M.; Konkova, Marina S.; Veiko, Roman V.; Umriukhin, Pavel E.; Martynov, Andrey V.; Kutsev, Sergey I.; Veiko, Natalia N.; Kostyuk, Svetlana V. (Frontiers in Genetics, 2019)
Introduction: Human satellite DNA is organized in long arrays in peri/centromeric heterochromatin. There is little information about satellite copy number variants (CNVs) in aging and replicative cell senescence (RS). Materials and Methods: Biotinylated pUC1.77 probe was used for the satellite III (f-SatIII) quantitation in leukocyte DNA by the non-radioactive quantitative hybridization for 557 subjects between 2 and 91 years old. The effect of RS and genotoxic stress (GS, 4 or 6 µM of K2CrO4) on the f-SatIII CNV was studied on the cultured human skin fibroblast (HSF) lines of five subjects. Results: f-SatIII in leukocyte and HSFs varies between 5.7 and 40 pg/ng of DNA. During RS, the f-SatIII content in HSFs increased. During GS, HSFs may increase or decrease f-SatIII content. Cells with low f-SatIII content have the greatest proliferative potential. F-SatIII CNVs in different individuals belonging to the different generations depend on year of their birth. Children (born in 2005–2015 years) differed significantly from the other age groups by low content and low coefficient of variation of f-SatIII. In the individuals born in 1912–1925 and living in unfavorable social conditions (FWW, the Revolution and the Russian Civil War, SWW), there is a significant disproportion in the content of f-SatIII. The coefficient of variation reaches the maximum values than in individuals born in the period from 1926 to 1975. In the group of people born in 1990–2000 (Chernobyl disaster, the collapse of the Soviet Union, and a sharp decline in the population living standard), again, there is a significant disproportion of individuals in the content of f-SatIII. A similar disproportion was observed in the analysis of a group of individuals born in 1926–1975 who in their youth worked for a long time in high-radioactive environment. Conclusion: In generations that were born and who lived in childhood in a period of severe social perturbations or in conditions of environmental pollution, we found a significant increase in leukocyte DNA f-SatIII variability. It is hypothesized that the change of the f-SatIII content in the blood cells reflects the body response to stress of different nature and intensity.